The Impact of US-China Trade War on Global Supply Chains. A Case Study of the Technology Industry. - Lyssenko, Nikita; Štěrbová, Ludmila, 1957-; Brellíková, Miriam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis aims to identify the impact of the U.S.-China trade war on U.S. semiconductors and Information and Communication Technology (ICT) industries, by showing how the conflict has reshaped supply chains, impacted the nature of trade relations, and examined sectoral performance. In this thesis the issues of national security, intellectual property, and technological interdependence are discussed in more detail. Disagreements in these aspects have led to the imposition of protective actions, both in the form of tariffs and non-tariff measures, which in turn have had a mixed impact on the manufacturing sectors of the semiconductor and ICT industries. In order to assess the impact of the trade war on selected U.S. manufacturing sectors, a quantitative analysis using advanced statistical research methods was conducted. The result of the analysis of shifts in supply chains in one of the most globalised industries indicates that the United States and allies dominating semiconductor-equipment supply and China commanding assembly, testing, and packaging, full decoupling proves impractical. Also, the impact of the measures taken on the sectoral performance of U.S. manufacturing is not unambiguous, as for high-tech industries innovation and labour quality are more important determinants of productive capacity. The conflict is driving selective reshoring and higher costs rather than a clean break, leaving both economies strategically rivalrous yet economically intertwined.
Vedoucí práce: Ludmila Štěrbová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses